2015
DOI: 10.1038/srep15242
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Haematuria and Clinical Outcomes in Patients With Stage 3–5 Nondiabetic Chronic Kidney Disease

Abstract: Microscopic haematuria is proposed as a prognostic factor for renal outcomes in patients with glomerulonephritis. However, the role of haematuria in patients with advanced chronic kidney disease (CKD) or heavy proteinuria has not been investigated. We divided 1799 patients with stage 3–5 nondiabetic CKD into 3 groups according to the results from 3 urinalyses: no haematuria (0–2 red blood cells [RBCs]/hpf ≥2 times), mild haematuria (2–5 RBCs/hpf ≥2 times) and moderate haematuria (≥5–10 RBCs/hpf ≥2 times). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…However, these studies exhibited heterogeneity, especially on the definition of hematuria. Our previous study has shown that hematuria according to ≥5–10 red blood cells per high power field (RBC/HPF), but not 2–5 RBC/HPF, was associated with NDRD 33 . This is supported by another report 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these studies exhibited heterogeneity, especially on the definition of hematuria. Our previous study has shown that hematuria according to ≥5–10 red blood cells per high power field (RBC/HPF), but not 2–5 RBC/HPF, was associated with NDRD 33 . This is supported by another report 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate logistic regression analysis was used to evaluate the relationships between parameters and rapid renal progression. The model was adjusted for age, sex, the eGFR, the log-transformed UPCR, hypertension, CV disease, MBP, HbA1c, hemoglobin, albumin, BMI, log-transformed cholesterol, log-transformed CRP, and phosphorus, according to the literature and our previous publications 33 , 34 .…”
Section: Methodsmentioning
confidence: 99%
“…A large-scale cohort study in Israel of young adults with hematuria demonstrated that persistent asymptomatic microscopic hematuria was a risk factor for ESRD onset [ 11 ]. A study of patients with stage 3–5 nondiabetic CKD demonstrated that microscopic hematuria was significantly associated with increased risk of ESRD, rapid renal function progression, and all-cause mortality, particularly in those with mild proteinuria [ 12 ]. Another study demonstrated that patients with advanced CKD with hematuria progressed significantly faster to ESRD as compared with patients with proteinuria alone [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these findings indicate that the cascade axis of MEKK2-p38 MAPK-IRF-1-TRADD-caspase 8 may play an important role in GMC apoptosis following exposure to sublytic C5b-9 in rat Thy-1N. The Journal of Immunology, 2017Immunology, , 198: 1104Immunology, -1118 M esangioproliferative glomerulonephritis (MsPGN), which is characterized by glomerular mesangial cell (GMC) apoptosis, proliferation, and extracellular matrix (ECM) secretion, is a representative nephritis that leads to chronic kidney disease (1)(2)(3)(4)(5), one of the most important risk factors for human end-stage renal disease and death (6)(7)(8). Although C5b-9, especially the sublytic C5b-9 complex, was found in the glomeruli of patients with MsPGN (9-12), it is not fully understood how it causes GMC damage.…”
mentioning
confidence: 99%